E-commerce quality model towards customers’ repurchasing intention in copper and brass small enterprises in Surakarta - Marwati, Fithri Setya (2025)
Small and medium-sized enterprises (SMEs) are vital to most economies, especially in emerging nations like Indonesia. With the rise of the digital economy, micro, small, and medium enterprises (MSMEs) have increasingly adopted e-commerce, yet many face obstacles such as poor website quality, limited e-service standards, and insufficient product quality. These issues reduce customer trust and hinder repurchasing behavior, particularly in brass and copper enterprises. This raises a practical question: how can e-commerce quality be enhanced to strengthen repurchasing intention a topic still underexplored in developing countries. Guided by the Stimulus–Organism–Response (S-O-R) framework, this study examines the influence of website quality, e-service quality, and product quality on customers’ repurchasing intention through customer satisfaction, while also assessing the moderating role of corporate image. A quantitative approach was employed using questionnaires distributed to 271 e-commerce customers of brass and copper products, with data analyzed via SmartPLS. Findings indicate that all three quality factors positively affect repurchasing intention through satisfaction. Furthermore, corporate image significantly moderates the satisfaction–repurchasing intention relationship. Theoretically, the study extends the S-O-R framework by validating the mediating role of customer satisfaction in e-commerce within a developing economy. Practically, it offers brass and copper enterprises a blueprint for enhancing digital competitiveness by improving e-commerce quality and cultivating a strong corporate image to foster customer loyalty and sustained growth.